2003
DOI: 10.17221/5786-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey and isolation of leptospires from small rodents and wild boars in the Republic of Croatia

Abstract: ABSTRACT:In total the samples of blood and kidneys of 379 small rodents and 154 wild swine were analysed. The antibodies to different serovars of leptospires were determined in 12.7% of small rodents, most o�en in the species Mus musculus (34.4%), A. agrestis (14.8%), A. flavicolis (10.8%), C. glareolus (9.4%) and A. sylvaticus (6.5%). Most frequent were the findings of antibodies to sv. pomona (27.1%), sv. sejroe (20.8%), and sv. australis (14.6%), and the antibodies to sv. hardjo, sv. saxkoebing, sv. tarasso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The high prevalence obtained in the category of 'guard/hunting dogs' can be explained by their close and R. Lindtner Knific et al: Seroprevalence of leptospiral antibodies in dogs frequent contact with wild and domestic pigs, which were found to be the most common carriers of Pomona. This serovar was found in wild boars in Croatia with a prevalence of 26% by CVETNIĆ et al, (2003) as well as in Slovenia with a prevalence of 45% by VENGUŠT et al (2008).…”
Section: Discussionmentioning
confidence: 86%
“…The high prevalence obtained in the category of 'guard/hunting dogs' can be explained by their close and R. Lindtner Knific et al: Seroprevalence of leptospiral antibodies in dogs frequent contact with wild and domestic pigs, which were found to be the most common carriers of Pomona. This serovar was found in wild boars in Croatia with a prevalence of 26% by CVETNIĆ et al, (2003) as well as in Slovenia with a prevalence of 45% by VENGUŠT et al (2008).…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the prevalence in rodents was lower than reported previously. In Croatia, Cvetnic´et al found 23% of house mice positive by serology [47] and Krojgaard and colleagues detected Leptospira spp. by PCR in 53% of sewer rats in Copenhagen [48].…”
Section: Pathogens Identifiedmentioning
confidence: 99%
“…Leptospirosis is an emerging/re-emerging, worldwide, contagious, bacterial zoonotic disease that affects all mammals, including humans, livestock and wildlife [ 1 , 2 ]. The disease is caused by different serovars of pathogenic species of the genus Leptospira [ 1 , 2 ], which is common in tropical and subtropical regions, wherever environmental conditions favour the survival and transmission of the bacterium [ 3 , 4 ]. Leptospirosis was first identified by Weil (1886) and Inada (1916) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%